2020
DOI: 10.3389/fmed.2020.592921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Chorionic Gonadotropin Injection Before Frozen Embryo Transfer on Pregnancy Outcomes in Endometriosis-Associated Infertility

Abstract: Purpose: The aim of this study was to investigate the effect of human chorionic gonadotropin (hCG) in hormone replacement (HT) regime for frozen thawed embryo transfer in women with endometriosis (EM).Methods: We performed a retrospective, database-search, cohort study and included data on EM patients who underwent frozen embryo transfer (FET) between January 1, 2009 and August 31, 2018. According to the protocols for FET cycle, the patients were divided into two groups: control group (n = 296) and hCG group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…It was speculated that hCG might enhance embryo implantation by interacting with molecules regulating endometrial receptivity. [26] In the present study, we found a significant increase in the pregnancy rate. However, the difference of live birth rate was not statistically significant, which may be related to the limit of designate time of our study, that some patients did not give birth at the end of study, which led to a relative increase in the live birth rate that was not statistically significant.…”
Section: Discussionsupporting
confidence: 62%
“…It was speculated that hCG might enhance embryo implantation by interacting with molecules regulating endometrial receptivity. [26] In the present study, we found a significant increase in the pregnancy rate. However, the difference of live birth rate was not statistically significant, which may be related to the limit of designate time of our study, that some patients did not give birth at the end of study, which led to a relative increase in the live birth rate that was not statistically significant.…”
Section: Discussionsupporting
confidence: 62%
“…When E2 is <2724.8 pg/mL, within the range 2724.8–4087.2 pg/mL, and >4087.2 pg/mL on trigger day, the live birth rates were 28.80%, 26.90% and 25.99%, respectively 12 . We noted that live birth rates reported in Duan et al's study were lower than those in the present study (45.4%) and other studies (which were within the range 35.6%–45.6% 19–22 ). Therefore, other factors, except for E2 on trigger day, might interfere with the live birth rates for FET cycles in Duan et al's 12 study.…”
Section: Discussioncontrasting
confidence: 57%
“…Undoubtedly, β-hCG is essential for the maintained of pregnancy. Moreover, β-hCG is also involved in the regulation of progesterone expression via the ERK1/2 pathway [21], and promote cytotrophoblast differentiation and endometrial stromal cell decidualization [22,23]. P transforms the E 2 -prepared endometrium into a secretory tissue and creates a hospitable environment for embryo attachment [24].…”
Section: Hormones Involved In Regulating Uterine Changes During Place...mentioning
confidence: 99%